Working With Children With Autism in General Physical Education: Useful Applied Behavior Analysis Concepts. Issue 9 (16th December 2021) - Felzer-Kim, Isabella Theresa; Campbell, Hannah; Vallabheneni, Neha; Peterson, Andrea; Hauck, Janet L.
Abstract : This article addresses six concerns raised by physical education teachers regarding working with children with Autism Spectrum Disorder: 1. Creating Engaging Programs; 2. Distracting/Negative Peer Relationships; 3. Emotional Regulation Difficulty; 4. Communicating the Task; 5. Narrow Focus and Adherence to Routines and Structure; and 6.Need for Support. The ABA concepts of functional behavior assessment, antecedent intervention, reinforcement, peer interventions, task analysis, and prompting are explained in the general physical education context with concrete ideas for practicing teachers.